A Case Report: Risperidone-Induced Lactation Nonpuerperal in Bipolar Patient - Rahajeng, Bangunawati; Maziyyah, Nurul; Nugrahaningtyas, Odilia Danti (Indonesian Journal of Clinical Pharmacy, 2023)
Risperidone is an atypical antipsychotic for acute and chronic schizophrenia and mania. In this case report, we report a rare side effect of risperidone, namely nonpuerperal lactation, where the common side effects of risperidone are insomnia, anxiety, headaches, and extrapyramidal symptoms. Lactation nonpuerperal is one of the rare side effects of risperidone, with an incidence in adults < 1%. We report the case of a 21-year-old woman. This woman was diagnosed with bipolar affective disorder with major depression and got risperidone, fluoxetine, trihexyphenidyl, and valproic acid for treatment. The first visit was at a teaching hospital on April 21, 2022. She had to control it within a month. At the first control on July 1, 2022, her condition improved. She had no complaints. On August 4, 2022, she came to the hospital and told the doctor that she had nonpuerperal lactation. We do a causality analysis that the side-effect is due to risperidone. From Naranjo’s analysis, we scored 6 for risperidone (probable). From the Liverpool algorithm, we concluded that risperidone probably caused lactation nonpuerperal. In this case, risperidone probably caused lactation nonpuerperal.